THE EFFECTIVENESS OF LAW NUMBER 32 OF 2009 CONCERNING ENVIRONMENTAL PROTECTION AND MANAGEMENT IN ADDRESSING WASTE IN BALI - I Nyoman Alit Putrawan; I Made Adi Widnyana (Samā Jiva Jnānam (International Journal of Social Studies), 2023)
The growing number of residents and tourists in Bali has created new problems in the field of environmental hygiene in the form of uncontrolled waste. Therefore, the government needs to apply Law number 32 of 2009 in dealing with these problems. The purpose of this study is to analyze the effectiveness of Law number 32 of 2009 in dealing with waste problems in Bali. The method used in this study is to use qualitative methods. The results of this study indicate that the implementation of the waste handling activity plan in the AMDAL that has been made is not in accordance with the planned activity plan causing the waste management and handling to be not carried out properly and also the community's right to an unhealthy environment due to the impact of the smell of waste handling at the TPA in Bali, namely submitting objections or complaints to related parties. However, the objections raised have not been taken seriously by the management and the existence of more than one management agency means that complaints cannot be handled properly